STAFF AND PERSONNEL POLICY IN COMMERCIAL BANKS IN THE SLOVAK REPUBLIC - Jágerová, Miroslava (Doprava a spoje, 2010)
Success of banking marketing depends to a great extent on selection, motivation and management of bank employees. The personnel policy task is to ensure that bank employees in compliance with the bank strategy meet attributes clients expect from them - qualification, credibility, politeness, communicativeness and perception. The bank gains a strong competition advantage by appropriate application of human resources management methods.